2020
DOI: 10.1111/mcn.13122
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caregiving capabilities are associated with child linear growth in rural Zimbabwe

Abstract: Between birth and 2 years, children's well-being depends on the quality of care they receive from caregivers, primarily their mothers. We developed a quantitative survey instrument to assess seven psychosocial characteristics of women that determine their caregiving ability ('maternal capabilities': physical health, mental health, decision-making autonomy, social support, mothering self-efficacy, workload and time stress, and gender norm attitudes). We measured maternal capabilities in 4,025 mothers and growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
11
0
5
Order By: Relevance
“…Among children in the control groups in this IPD, those whose mothers had lower scores for depressive symptoms had slightly higher mean LAZ and HCZ than those whose mothers were in the top quartile for depressive symptoms (a difference of ∼ −0.10 Z), suggesting that the former subgroup was less vulnerable, which is inconsistent with a greater potential to benefit. However, in the SHINE trial in Zimbabwe ( 91 ), the effect of the intervention on LAZ was greater among children of mothers who scored ≥12 on the Edinburgh Postnatal Depression Scale [a cutoff validated against clinically diagnosed major depression in Zimbabwean women ( 61 )], such that the difference in mean LAZ between children of depressed and nondepressed mothers observed in the control group was not evident in the intervention group. This may reflect amelioration by SQ-LNSs of the adverse influence of maternal depression on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Among children in the control groups in this IPD, those whose mothers had lower scores for depressive symptoms had slightly higher mean LAZ and HCZ than those whose mothers were in the top quartile for depressive symptoms (a difference of ∼ −0.10 Z), suggesting that the former subgroup was less vulnerable, which is inconsistent with a greater potential to benefit. However, in the SHINE trial in Zimbabwe ( 91 ), the effect of the intervention on LAZ was greater among children of mothers who scored ≥12 on the Edinburgh Postnatal Depression Scale [a cutoff validated against clinically diagnosed major depression in Zimbabwean women ( 61 )], such that the difference in mean LAZ between children of depressed and nondepressed mothers observed in the control group was not evident in the intervention group. This may reflect amelioration by SQ-LNSs of the adverse influence of maternal depression on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial motivation for evaluating the Friendship Bench in rural Zimbabwe stemmed from the SHINE trial (Humphrey et al ., 2019 ), which identified a substantial burden of depression in pregnancy and a lack of locally available interventions (Tome et al ., 2020 ). Previous studies have shown that maternal depression contributes to child undernutrition (Surkan et al ., 2011 ), and the UNICEF framework highlights the central role of maternal caregiving in promoting healthy growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that maternal depression contributes to child undernutrition (Surkan et al ., 2011 ), and the UNICEF framework highlights the central role of maternal caregiving in promoting healthy growth and development. In SHINE, we found that the randomised infant feeding intervention ameliorated the adverse impact of depression on child growth (Tome et al ., 2020 ). However, we did not explicitly include an intervention to tackle maternal depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations